2013
DOI: 10.1111/jch.12163
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Modeling of Patient and Physician Determinants of Blood Pressure Outcomes in Adherent vs Nonadherent Hypertensive Patients: Pooled Analysis of 6 Studies With 14,646 Evaluable Patients

Abstract: The authors used pooled data from 6 valsartan-related studies including 3983 adherent and 10,663 nonadherent patients to evaluate blood pressure (BP) outcomes in both groups after 90 days of treatment, applying hierarchical linear and logistic regression to identify determinants of BP outcomes. The principal findings were that: (1) BP outcomes were consistently better in adherent patients; (2) approximately a quarter of the variance in 90-day BP values was attributable to a physician class effect; (3) common a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Adherence was associated with lower SBP and DBP values and higher odds of achieving BP control. In an analysis of this same pooled data set comparing adherent and nonadherent patients, BP values and BP control rates were consistently better among adherent patients [10]. Interestingly, this analysis revealed that adherence to antihypertensive regimens may be a function of prior treatment-line failure, severity of illness, and patients experiencing (major) health problems related to their hypertension and/or diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence was associated with lower SBP and DBP values and higher odds of achieving BP control. In an analysis of this same pooled data set comparing adherent and nonadherent patients, BP values and BP control rates were consistently better among adherent patients [10]. Interestingly, this analysis revealed that adherence to antihypertensive regimens may be a function of prior treatment-line failure, severity of illness, and patients experiencing (major) health problems related to their hypertension and/or diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Такий результат дозволяє припустити, що для лікування зазначеної групи пацієнтів раціонально застосовувати структурований підхід до антигіпер-тензивної терапії, що передбачає її вчасну інтенсифі-кацію та використання фіксованих медикаментозних комбінацій від початку лікування. За нашими даними висока прихильність до лікування була чинником, що через 6 місяців засто-сування алгоритмізованої терапії незалежно асоці-ювався як з контролем офісного, так і з контролем домашнього АТ, що узгоджується з результатами інших досліджень [6, 7,19]. Відомо, що завелика кількість медикаментозних засобів негативно впли-ває на комплаенс пацієнтів.…”
Section: результати дослідженняunclassified
“…In view of these reports indicating that both patients and clinicians may share responsibility for poor BP results, it is interesting to consider the article by Dr Ivo Abraham and colleagues that looked at a meta‐analysis of 14,646 patients to evaluate whether physicians or patients might be primarily responsible for inadequate responses to treatment. As already discussed, hypertension is an asymptomatic disease and is particularly susceptible to nonadherence, which has been reported in up to 50% of patients with this condition .…”
Section: Improving Treatmentmentioning
confidence: 99%